Tectonic influence of Cenozoic post-rift alkaline magmatic intrusions on the onshore basement of the Campos and Santos basins, SE Brazil - Oliveira, Maria José Resende; Schmitt, Renata da Silva; Araújo, Mário Neto Cavalcanti de; Valente, Sérgio de Castro; Savastano, Vitor Lamy Mesiano; Inocêncio, Leonardo Campos [UNESP]; Carmo, Isabela de Oliveira (Elsevier, 2023)
This study focuses on the tectonic control of post-rift Eocene alkaline intrusions that outcrop in the Atalaia Peninsula, SE Brazil, on the onshore limit of both the Campos and Santos basins, the most prolific Brazilian oil basins. To investigate these tectonic-magmatic processes, high-resolution unmanned aerial vehicle (UAV) images, structural field data, and geochronological analyses were performed. This study characterized several alkaline lithotypes (syenites, N–S and NW–SE trachytes, NW–SE lamprophyres, and E–W phonolites dikes), cutting a N–S oriented Paleoproterozoic orthogneiss basement and NE–SW tholeiitic dikes. A new Ar–Ar age of 53.82 ± 0.7 Ma was obtained on phlogopite from one lamprophyre dike. Geometric and dynamic analysis indicate that these alkaline intrusions are synchronous and their emplacements can be explained by a sub-horizontal NNE–SSW intraplate extension linked to a sub-vertical σ1. Magma rising occurred by forceful injection through transcrustal sets of discontinuities that reached the mantle. Strike to oblique-slip and late normal faults support an anticlockwise rotational extension direction after emplacement. These alkaline tectonic-magmatic dynamics may have caused an isostatic response, influencing the evolution of the abutting offshore basins while triggering a large influx of sediments during the Paleocene-Eocene.
Keywords: Alkaline intrusions; Atalaia Peninsula; Brazilian margin; Cenozoic tectonics; Lithospheric extension; UAV geological mapping